Clostridium butyricum potentially improves inflammation and immunity through alteration of the microbiota and metabolism of gastric cancer patients after gastrectomy - Cao, Wenjie; Zheng, Cihua; Xu, Xuan; Jin, Rui; Huang, Feng; Shi, Meng; He, Zhipeng; Luo, Yufeng; Liu, Lulin; Liu, Zhaoxia; Wei, Jing; Deng, Xiaorong; et al. (Frontiers in Immunology, 2022)
Background Gastrectomy is the most effective treatment to improve the clinical survival rate of patients with gastric cancer. However, the pathophysiological changes caused by gastrectomy have seriously affected the postoperative recovery. Methods In the present trial, Ataining (containing C. butyricum, CGMCC0313.1) was applied in patients after gastrectomy to investigate the effect of C. butyricum on the early postoperative recovery by monitoring the inflammatory immune response with blood indicators, detecting the gut microbiota with high-throughput sequencing, and analyzing the short-chain fatty acids (SCFAs) with targeted metabolomics. This study is registered with the number ChiCTR2000040915. Results Our outcomes revealed that C. butyricum had significantly reduced the number of Leucocyte (P < 0.001), the percentage of Neutrophil (P < 0.001), the expression of IL-1β (P < 0.01), IL-6 (P < 0.05), and TNF-α (P < 0.01), while markedly enhanced the immunity indexes (immunoglobulin and lymphocyte) (P < 0.05) and nutrition indexes (albumin and total protein) (P < 0.05). In addition, the use of the C. butyricum greatly enriched the relative abundance of beneficial bacteria Bacteroides, Faecalibacterium and Gemmiger, while the abundance of pathogenic Streptococcus, Desulfovibrio and Actinomyces were markedly decreased at genus level. We also observed significant up-regulation of SCFAs, including acetic acid, propionic acid, butyric acid and isobutyric acid, after C. butyricum administration in patients receiving gastrectomy. Conclusion Therefore, evidence supported that oral administration of C. butyricum after gastrectomy can reduce early postoperative inflammation, enhance immune ability, restore intestinal microbiota eubiosis, increase intestinal SCFAs, reduce the occurrence of postoperative complications, and ultimately promote the early recovery of the patient. Clinical trial registration http://www.chictr.org.cn/, identifier (ChiCTR2000040915).